Efficiency of the Use of Humidified Gas Fuel and Oxidizing Mixture - B. S. Soroka; N. V. Vorobyov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
The influence of hydration of the components of combustion (air-oxidizer and – in some cases – fuel) including hydration in the conditions of substitution of natural gas by alternative gas fuels, viz. by coke blast furnace mixture and natural blast furnace mixture – on energy efficiency of the use of different fuels has been determined. Calculations of fuel saving for substitution of natural gas (NG) by wet process gas (blast furnace gas (BFG), coke gas (CG), their mixtures) were performed taking into account real technological parameters (on the example of a specific metallurgical plant). All the calculations were performed within the framework of the author’s methodology on fuel substitution grounded on the 1st and the 2nd laws of thermodynamics. The analysis of possibility for saving or overspending NG is performed in the conditions of preservation of the flow of the used total enthalpy (as the main requirement of the methodology that had been proposed) and of taking into account the corresponding efficiency of fuel use. The calculation of the required heat flow of natural gas combustion depending on the content of wet blast furnace gas in NG + BFG mixtures for the cases of NG substitution by process gases has been carried out. It is established that the presence of moisture in the fuel-oxidation mixture always reduces the efficiency of the combustion chamber or the energy process and the unit. In order to increase the efficiency of a high-temperature furnace (boiler), it is necessary to provide heating of combustion components when utilizing the heat of the outgoing combustion products. It is shown that the efficiency of the fuel-using system can be significantly increased when the potential (excess total enthalpy) of the working fluid (combustion products) is activated. There are additiоnal benefits due to the fact that the existing heat of products of combustion with humid air in a full range of temperatures – from the theoretical combustion temperature to ambient temperature under conditions of equilibrium, including account of the heat of condensation – increases with increasing moisture content of the initial components of combustion, viz. air-oxidizer and/or fuel gas.